association between daily protein intake and outcome events only exist in patients with inflammation on peritoneal dialysis - Jie Dong; Yanjun Li; Rong Xu (The Korean Society of Nephrology, 2012)
Whether the association between decreased protein intake and raised risk for all-cause, cardiovascular death and peritonitis is confounded by inflammation status is unknown. This study aimed to explore the predicting role of daily protein intake (DPI) in above outcome events in patients with and without inflammation respectively. Our study enrolled 305 incident patients who could be followed regularly. Demographic data was collected at baseline. Biochemical, dietary and nutritional data, dialysis adequacy were measured at the baseline and thereafter at regular intervals. A total of 127 patients died during the 44.5-month follow-up. Total 129 first-episode peritonitis were observed. Patients with high tertile of baseline DPI had significantly higher serum albumin, prealbumin, hemoglobin, lean body mass and hand grip strength compared to low tertile group (P<0.05∼0.001). They also had significantly lower risk for all-cause, cardiovascular death and first-episode peritonitis than low tertile group adjusted for commonly recognized confounders. When the whole cohort was divided into two groups according to the C-reactive levels higher or lower than 3 mg/L, the predicting role of baseline DPI only existed in patients with inflammation status.Conclusions: The decreased DPI predicted the increase risk for all-cause and cardiovascular death, and the first-episode peritonitis only in PD patients with chronic inflammation. The target of DPI may differ for patients with and without chronic inflammation